2011
DOI: 10.1590/s0102-09352011000300037
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência do vírus da leucemia felina em Felis cattus em Belo Horizonte

Abstract: Blood samples from 1,072 domestic cats of nine administrative regions of Belo Horizonte, MG, were collected and tested using PCR nested for the occurrence of feline leukemia virus (FeLV). Overall occurrence was 47.5% (507/1072) being North (68.1%) and East (54.4%) the most prevalent areas. Epidemiological data showed that FeLV infection was very common among examined cats and breed neither gender nor were predisposing factors for FeLV. The results suggest that the agglomeration of a large number of cats in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 8 publications
1
8
1
3
Order By: Relevance
“…Among FeLV + animals, a greater prevalence was observed between 1 and 5 years of age, similar to the one found in the city of São Paulo, which observed a significant number of positive animals between 3 and 6 years of age (Jorge et al, 2011). This high proportion of FeLV + felines in young adults and the absence of seropositive individuals above 11 years of age may be justified by the high mortality rate in infected young animals, as well as being more susceptible, while older cats are more resistant (Coelho et al, 2011;Hartmann, 2012). However, Westman et al (2016) demonstrated that older cats are as susceptible to infection as young ones.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Among FeLV + animals, a greater prevalence was observed between 1 and 5 years of age, similar to the one found in the city of São Paulo, which observed a significant number of positive animals between 3 and 6 years of age (Jorge et al, 2011). This high proportion of FeLV + felines in young adults and the absence of seropositive individuals above 11 years of age may be justified by the high mortality rate in infected young animals, as well as being more susceptible, while older cats are more resistant (Coelho et al, 2011;Hartmann, 2012). However, Westman et al (2016) demonstrated that older cats are as susceptible to infection as young ones.…”
Section: Discussionsupporting
confidence: 80%
“…The prevalence of 12.32% for FIV and 5.80% for FeLV in Fortaleza-CE varied from the results found, through serological methods, in other cities of Brazil: 0.78% and 0.36% in São Paulo (Santos et al, 2013), 5.63% and 0.33% in Araçatuba-SP (Sobrinho et al, 2011) for FIV and FeLV, respectively, and 38.3% in Pelotas and Rio Grande-RS for FeLV (Meinerz et al, 2010). Felines with FIV and FeLV detected by PCR or nested PCR were 4.14% and 47.0% in Belo Horizonte (Teixeira et al, 2007;Coelho et al, 2011), respectively, and 15.70% for FIV in Pelotas -RS (Silva et al, 2014), and there was no presence of co-infection of these diseases in these studies. The discrepancy between the values found by the authors may reflect the methods used, since serological techniques show high specificity and sensitivity, with false negative results in cats regressively infected with FeLV and false positives for FIV due to the presence of maternal antibodies, especially in cats younger than six month-old (Hosie et al, 2009;Little et al, 2011).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…On the other hand, in studies on hospitalized animals and animals showing clinical and laboratory signs compatible with these infections, the prevalence values are commonly found to be higher (Macieira et al, 2008;Coelho et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This explains the variations of seroprevalence from 2.5 to 31.3% for FIV and from 2.3 to 30.4% for FeLV that have been found in studies from different parts of the world (Arjona et al, 2000;Levy et al, 2006;Bande et al, 2012). In Brazil, the seroprevalence ranges from 5.6 to 16.7% for FIV and from 0.33 to 32.5% for FeLV (Teixeira et al, 2007;Macieira et al, 2008;Sobrinho et al, 2011) and, additionally, the infection rates found using molecular tests have ranged from 2 to 15.7% for FIV and from 0.5 to 47.5% for FeLV (Coelho et al, 2011;Marçola, 2011;Silva et al, 2014).…”
Section: Introductionmentioning
confidence: 88%